THE PANDEMIC CONTEXT FOCUSED ON EDUCATION - Ferreira Borges, Josicléia; Xavier Dantas, Veridiana; Ventura de Lima Pinheiro, Danielle (Revista Gênero e Interdisciplinaridade, 2025)
This article arose from the interest of the researcher, who is a teacher in the Early Years of Basic Education in the Public School System at a Municipal School in Caaporã, in the interior of the State of Paraíba, where she has worked for 25 years. Currently, due to special needs, I am on leave, away from the profession. However, I witnessed the great difficulty of students learning through remote teaching, in addition to the noticeable obstacles understood by teachers, without support and adequate training to experience the pandemic context, the difficulty of using technologies for the development of teaching/learning was notorious, being an obstacle not only for teachers, but also for the school community.